Milking System Changeover and Effects Thereof on the Occurrence of Intramammary Infections in Dairy Cows - Pauline Katthöfer; Svenja Woudstra; Yanchao Zhang; Nicole Wente; Franziska Nankemann; Julia Nitz; Jan Kortstegge; Volker Krömker (Ruminants)
Adopting a new milking system at a dairy farm causes various changes. This study examined the impact on udder health when changing from a conventional milking system to an automatic milking system. For this purpose, quarter milk samples were taken six times from 138 cows at one conventional dairy farm in Northern Germany over a five-week period around the time of the milking system changeover. To assess udder health, the absolute number of new intramammary infections and the causative pathogen genera and species were analysed for each individual study time point. Pathogen species were detected using matrix-assisted laser desorption ionisation time-of-flight, and the infection dynamics were analysed using two Poisson regression models. In addition, the prevalence and incidence of new intramammary infections and the infection dynamics of the four most frequently isolated pathogen species were calculated. Mixed models were used to determine the development of the new infection rate, the somatic cell count, the teat-end condition, and the udder hygiene between the individual study time points and to compare the new infection rate before and after the changeover of the milking system. After the automatic milking system had been installed, a significant increase in the quarter-level somatic cell count occurred (p < 0.001). Two days before the installation of the automatic milking system, the mean quarter-level somatic cell count was 11,940 cells/mL milk; one sampling date later, 8 days after the changeover, a mean quarter-level somatic cell count of 60,117 cells/mL milk was measured. The significant increase in somatic cell count was probably caused by the time between the last milking and the quarter milk sampling. Additionally, significantly more udders were scored as clean 8 days (95%) and 15 days (96%) after the changeover of the milking system compared to at the last sampling date (88%). Also, significantly more teat ends were classified as free of hyperkeratosis 15 days (80%) compared to 22 days (67%) after the changeover of the milking system. The highest number of absolute new intramammary infections was detected 8 days before the transition of the milking system (28.6%). The lowest number of absolute new intramammary infections occurred 8 days after the change to the automatic milking system (11.0%). Minor mastitis pathogens, such as non-aureus staphylococci and coryneform bacteria, were mainly responsible for the development of new intramammary infections. The most frequently isolated pathogen species were Staphylococcus sciuri, Staphylococcus chromogenes, Staphylococcus haemolyticus, and Corynebacterium amycolatum, with a prevalence of up to 23.9, 10.7, 8.4, and 5.3%, respectively. By comparing the new infection rate before and after the changeover of the milking system, it was possible to establish that the changeover to the automatic milking system had no significant influence on the new intramammary infection rate (p = 0.988). Therefore, this trial confirmed that the changeover from a conventional milking system to an automatic milking system had no negative influence on udder health.